Calcule a expressão 61-(54-24:4)=
Soluções para a tarefa
Respondido por
5
Boa tarde.
![61-(54-24:4)=
61 - (54 - 6) =
61 - (48) =
61 - 48 = 13 61-(54-24:4)=
61 - (54 - 6) =
61 - (48) =
61 - 48 = 13](https://tex.z-dn.net/?f=61-%2854-24%3A4%29%3D+%0A%0A61+-+%2854+-+6%29+%3D+%0A%0A61+-+%2848%29+%3D+%0A%0A61+-+48+%3D+13)
(-).(+) = -
Bons estudos! ( ͡° ͜ʖ ͡°)
(-).(+) = -
Bons estudos! ( ͡° ͜ʖ ͡°)
Perguntas interessantes
Física,
11 meses atrás
Matemática,
11 meses atrás
Geografia,
11 meses atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
História,
1 ano atrás
Português,
1 ano atrás